MODERN STATE OF ACCOUNTING AND TAXING OF FRANCHISING IN A RESTAURANT BUSINESS - A. Tsyutsyak (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article covers the nature and the peculiarities of taxing and the order of operation depicting in the system of restaurant bookkeeping according to the franchising agreement. The franchisee expenses are offered to interpret as the expenses of operations' coordination.